2015
DOI: 10.1164/rccm.201501-0020oc
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Receptor for Advanced Glycation End-Products Predicts Impaired Alveolar Fluid Clearance in Acute Respiratory Distress Syndrome

Abstract: Our results indicate that sRAGE levels could be a reliable predictor of impaired AFC during ARDS, and should stimulate further studies on the pathophysiologic implications of RAGE axis in the mechanisms leading to edema resolution. Clinical trial registered with www.clinicaltrials.gov (NCT 00811629).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 46 publications
4
143
0
1
Order By: Relevance
“…Thus, it seems reasonable to supplement increasing ARDS awareness with biomarkers of acute lung damage like SPD and probably others. In a rat model of ARDS, soluble receptor for advanced glycation end products (sRAGE) seemed to reflect alveolar type I cell injury, and this was also observed in humans [29, 30], and recently, it has been demonstrated that a strong negative correlation exists between alveolar fluid clearance rate and plasma sRAGE in a murine model as well as in humans [31]. Thus, sRAGE and SPD may provide complementary information on the pathophysiological changes taking place in the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems reasonable to supplement increasing ARDS awareness with biomarkers of acute lung damage like SPD and probably others. In a rat model of ARDS, soluble receptor for advanced glycation end products (sRAGE) seemed to reflect alveolar type I cell injury, and this was also observed in humans [29, 30], and recently, it has been demonstrated that a strong negative correlation exists between alveolar fluid clearance rate and plasma sRAGE in a murine model as well as in humans [31]. Thus, sRAGE and SPD may provide complementary information on the pathophysiological changes taking place in the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…As the ALI/ARDS resolves in patients, plasma sRAGE levels also fall, suggesting that sRAGE can act not only as a marker of disease severity and prognosis but also as a marker of resolving disease [99,100]. …”
Section: Rage In Pulmonary Diseasesmentioning
confidence: 99%
“…Small RCTs have shown that IOLPV causes an attenuated release of local and systemic inflammatory mediators after cardiopulmonary bypass, major abdominal surgery, and esophagectomy 198687. In open abdominal surgery, investigators have shown improvements in both intraoperative and postoperative pulmonary mechanics.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%